Analysis of the influence of intellectual capital and bank risk on the performance of maqashid sharia based Islamic banking in Indonesia - Dea Feby Septiani; Imam Yahya; Setyo Budi Hartono; Tri Widyastuti Ningsih; Fiina Ishmatul Maula (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
Purpose - This study aims to determine the effect of intellectual capital and bank risk on the performance of maqashid sharia based Islamic banking in Indonesia (An empirical study on Islamic Commercial Banks registered in Financial Services Authority (OJK) in 2017-2019).Method - This study used secondary data and used the multiple linear regression analysis method. The sample used was the purposive sampling method with the results of 12 Islamic Commercial Bank (BUS) as a sample of 14 BUS populations.Result - The results of this study stated that iB-VACA had a significant adverse effect on MSI variable; iB-VAHU had a positive but not significant effect on MSI variable; iB-STVA had an insignificant negative effect on MSI variable; CAR had an insignificant negative effect on MSI variable, and FDR had a positive but not significant effect on MSI variable.Implication - Islamic banking is advised to optimize its intangible assets and estimate the risks that will occur, as well as to pay attention to its sharia objectives to increase company value and performance.Originality - The secondary data source of this research is obtained from the official website of OJK, and financial report data is obtained from the website of each BUS.